Gambaran Pola Rugae Palatal pada Anak dan Ibu Kandung di Wilayah Kabupaten Jember - Wahyu Putri Maulidha (Fakultas Kedokteran Gigi, 2026)
Forensic odontology is a branch of dentistry that plays an important role in the process of identifying individuals, especially in situations where identity is difficult to determine, such as in cases of mass disasters. One of the secondary identification method that can be used is rugoscopy, which is the examination of palatal rugae patterns. Palatal rugae patterns are unique, relatively stable, and have the potential for inheritance, so they can be used to trace kinship relationships of the native. This study aims to determine the palatal rugae patterns of a child and the biological mothers in the Jember Regency based on the shape and unification of palatal rugae according to Thomas and Kotze (1983) classification. This is a cross-sectional study. The research sample consisted of 50 pairs of children and biological mothers selected using quota sampling techniques. Data were collected through intraoral clinical photography of the maxilla, then analyzed to determine the shape and unification of palatal rugae. Data analysis was performed descriptively and statistically using the Chi-Square test with p value < 0.05. The results showed that the most common shape of palatal rugae found in mothers and children was wavy, while the circular shape was the least common. Based on the results of the Chi-Square test, the wavy pattern shows a significant inheritance relationship between mother and child. In the unification category, the divergent pattern shows a significant relationship, while convergent unification does not show a statistically significant relationship. The conclusion of this study showed that there were similarities in palatal rugae patterns between mothers and children, especially in wavy shapes and divergent unification. Thus, rugoscopy has the potential to be used as a secondary identification method in forensic odontology, especially when antemortem data is available.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: rugoscopy; palatal rugae pattern; inheritance; mother and child